Brain activity associated with the rubber foot illusion. (16th March 2020) - Matsumoto, Nanae; Nakai, Ryusuke; Ino, Tadashi; Mitani, Akira
Highlights: Brain activity during the rubber foot illusion was examined. The prefrontal cortex, parietal cortex, and cerebellum were conjointly activated. Activated brain-area distribution was similar to that in the rubber hand illusion. These areas may be associated with the internal representation of one's own body. Abstract: The internal representation of the body is constantly updated by sensory information based on interactions with the environment. The internal representation of the hand can be experimentally manipulated with the rubber hand illusion (RHI) paradigm. Brain activity during the RHI provides insight into the neural mechanisms underpinning the reconstruction of the internal representation of the hand. Recently, the RHI paradigm has been employed for the lower limb, revealing that the illusion is also induced in the lower limb (rubber foot illusion; RFI). However, the neural correlates of the RFI remain unknown. We used functional magnetic resonance imaging (fMRI) to examine brain activity during the RFI. Forty-four healthy volunteers participated in the fMRI experiment. Significant increases in activation were observed in the bilateral medial and middle frontal gyri, left supplemental motor area, bilateral inferior parietal lobuli, precunei, calcarine cortices, and cerebellar hemispheres; and in the vermis and bilateral thalami during the right RFI. During the left RFI, significant increases in activation were observed in the bilateral medial, middle, and superior frontal gyri; left inferior frontal gyrus and supplemental motor area, bilateral inferior parietal lobuli and middle temporal gyri, and in the left cerebellar hemisphere, vermis, and bilateral thalami. Conjunction analysis revealed that the prefrontal cortex including the bilateral medial and middle frontal gyri, parietal cortex including the bilateral inferior parietal lobuli, and cerebellum including the bilateral cerebellar hemispheres and vermis were conjointly activated during the right and left RFIs. The distribution of co-activated brain areas during the RFI was similar to the previously reported distribution of brain areas activated during the RHI. Co-activation of these brain areas may be associated with the reconstruction of the internal representation of the body. The fact that these areas are activated both in the RFI and RHI will have implications for the treatment of patients with disturbed internal bodily representation.